Effects of preexisting and new-onset diabetes mellitus on clinical outcomes of patients with heart failure - Ching-Pei Chen; Szu-Chi Chien; Chew-Teng Kor; Che-Ming Hsu (Annals of Medicine)
Background Diabetes mellitus (DM) is a common comorbidity in heart failure (HF), but the impact of new-onset DM on HF outcomes remains unclear. This study evaluated the effects of DM status on hospitalization for HF (HHF), major adverse cardiac events (MACEs), and mortality in HF patients.Methods We conducted a retrospective cohort study of patients newly diagnosed HF at Changhua Christian Hospital, Taiwan, from 2011 to 2021. Patients were grouped as non-DM (n = 1477), preexisting DM (n = 1488), and new-onset DM (n = 328). Inverse propensity score weighting was applied to balance covariates.Results Compared to the non-DM group, the preexisting DM was associated with higher risks of HHF [hazard ratio (HR), 1.13; 95% confidence interval (CI), 1.02–1.25], MACEs (HR, 1.22; 95% CI, 1.00–1.49), all-cause mortality (HR, 1.17; 95% CI, 1.01–1.36), and cardiovascular death (HR, 1.54; 95% CI, 1.15–2.06). The new-onset DM group showed a significantly higher risk of HHF (HR, 1.24; 95% CI, 1.01–1.51) and MACEs (HR, 1.22; 95% CI, 1.00–1.49), with nonsignificant trends toward increased all-cause mortality (HR, 1.08; 95% CI, 0.79–1.48) and cardiovascular death (HR, 1.36; 95% CI, 0.74–2.48).Conclusion In HF patients, preexisting DM is associated with worse outcomes across multiple endpoints. New-onset DM also elevates risks of HHF and MACE, though its effect on mortality is less clear. Although our study, utilizing electronic medical record data, revealed a different pattern compared to the Danish registry, the findings emphasize the need for individualized management strategies based on DM status in HF care.